TEACHING METHODS OF QUANTITATIVE NUMERALS IN THE KOREAN LANGUAGE (European Journal of Interdisciplinary Research and Development, 2025)
This article thoroughly analyzes effective methods for teaching quantitative numerals in the Korean language. Numerals hold significant grammatical value and play a crucial role in helping learners express themselves clearly and accurately during communication. The article explores the main types of Korean numerals, their usage, pronunciation features, and methods for effectively teaching them. Emphasis is placed on the importance of using interactive methods, communicative approaches, and visual materials in the educational process. The paper also examines how to teach context-appropriate use of numerals and strategies to reduce common learner errors. The findings contribute to enhancing the effectiveness of didactic methods in Korean language instruction.